The Role of Ciliwung River School Management in Tourism Sustainability - Rizki Nurul Nugraha; Fauzi Achmad Riyadi; Salsabila Shafa; Suci Ramadhanti (West Science Social and Humanities Studies, 2024)
The researcher chose the title The Role of Ciliwung River School Management in Tourism Sustainability because he wanted to see the role of MAT PECI in the accessibility management system to create sustainable tourism at the Ciliwung River School. The obstacle is the infrastructure of the Ciliwung River School, namely accessibility to the Ciliwung River School, so researchers want to know the sustainability of tourism which will impact the environment and local communities. Ciliwung River School is located on Jalan. Current No. 99 Ex. Srengseng Sawah District. Jagakarsa, South Jakarta. This research uses descriptive qualitative methods with SWOC analysis. The research results show that well-planned and implemented management for the community plays a vital role in the Ciliwung River School which can increase awareness of the surrounding community and the sustainability of tourism. Based on the results of this research, the management of the Ciliwung River School applies the concepts of planning, organizing, implementing, and controlling to increase location accessibility and ensure a positive visitor experience. This research aims to analyze the role of management at the Ciliwung River School for tourism sustainability.